Effect of initial grain size on microstructure and toughness of intercritical heat-affected zone of a low carbon steel - Eroglu, M; Aksoy, M (Elsevier Science Sa, 2000)
In this study, the effects of initial grain size with the varying heat inputs on the microstructure and toughness of intercritical heat-affected zone (HAZ) of a low-carbon steel were investigated. In the welding experiments, SAE 1020 steel specimens in hot-rolled (original), in grain-refined and in grain-coarsened conditions were welded by a submerged are welding machine with the heat inputs of 0.5, 1 and 2 kJ mm(-1). Following the welding, microstructure, hardness and toughness of the intercritical HAZs of the specimens were investigated. The determination of microstructure and measurement of hardness in the intercritical HAZs were performed on the samples taken from the welded specimens, while toughness values were obtained using the weld thermal simulation technique. From the results, we tried to establish a relationship between the heat input, initial grain size, microstructure, hardness and toughness of the intercritical HAZ. From the results of the toughness tests and microstructural observation, it was seen that the fine initial grain size was effective on the formation of ductile phases and on the higher toughness, whereas the coarse initial grain was effective on the formation of brittle phases and on the lower toughness at the same heat input. As a result, considering the microstructure, hardness and toughness of the intercritical HAZ, a higher heat input for both the coarse initial grain size and fine initial grain size gave good results. However, it was also seen that a lower heat input can be used in the welding of low carbon steel with fine initial grain size with respect to the toughness of the intercritical HAZ. (C) 2000 Elsevier Science S.A. All rights reserved.
Keywords: initial grain size; intercritical heat-affected zone (HAZ); microstructure; toughness; hardness